Switching the reaction pathways of electrochemically generated β-haloalkoxysulfonium ions – synthesis of halohydrins and epoxides - Shimizu, Akihiro; Hayashi, Ryutaro; Ashikari, Yosuke; Nokami, Toshiki; Yoshida, Jun-ichi (Beilstein Journal of Organic Chemistry, 2015)
β-Haloalkoxysulfonium ions generated by the reaction of electrogenerated Br+ and I+ ions stabilized by dimethyl sulfoxide (DMSO) reacted with sodium hydroxide and sodium methoxide to give the corresponding halohydrins and epoxides, respectively, whereas the treatment with triethylamine gave α-halocarbonyl compounds.
Keywords: DMSO; electrosynthesis; epoxides; halohydrins; halogen cations